Developing technical support and strategic dialogue at the country level to achieve Primary Health Care-based health systems beyond the COVID-19 era - Cheong Chi Mo, Jeremy; Shah, Archana; Downey, Casey; Genay-Diliautas, Sophie; Saikat, Sohel; Mustafa, Saqif; Meru, Nikon; Dalil, Suraya; Schmets, Gerard; Porignon, Denis (Frontiers in Public Health, 2023)
Pursuing the objectives of the Declaration of Alma Ata for Primary Health Care (PHC), the World Health Organization (WHO) and global health partners are supporting national authorities to improve governance to build resilient and integrated health systems, including in recovery from public health stressors, through the long-term deployment of WHO country senior health policy advisers under the Universal Health Coverage Partnership (UHC-P). For over a decade, the UHC-P has progressively reinforced, via a flexible and bottom-up approach, the WHO strategic and technical leadership on UHC, with more than 130 advisers deployed in WHO Country and Regional Offices. This network has enabled the WHO country offices to strengthen their support on PHC and UHC to Ministries of Health and other national authorities as well as global health partners, by building technical capacities to lead health policy cycles and generate political commitment, evidence and dialogue for policy making processes, whilst creating synergies and harmonization between stakeholders. The policy dialogue at country level has been instrumental for ensuring a whole-of-society and whole-of-government approach, beyond the health sector, through community engagement and multisectoral actions. Relying on the lessons learned during the 2014-2016 Ebola outbreak in West Africa and in fragile, conflict-affected and vulnerable settings, health policy advisers played a key role during the COVID-19 pandemic to support countries on health systems response and early recovery. They brought together technical resources to contribute to the COVID-19 response and to ensure the continuity of essential health services, through a PHC approach in health emergencies. During the last decade, health policy advisers have been described as crucial assets by WHO Regional and Country Offices in the integration of health systems to enhance their resilience. This policy and practice review, including from the following country experiences Colombia, Islamic Republic of Iran, Lao PDR, South Sudan, Timor Leste and Ukraine, provides operational and inner perspectives on strategic and technical leadership provided by WHO to assist Member States in strengthening PHC and essential public health functions for resilient health systems. It aims to demonstrate and advise lessons and good practices for other countries in their health systems recovery phase.